TRANSFORMATION OF THE PROCESS OF TEACHING INFORMATION TECHNOLOGY IN MEDICAL EDUCATION - Штернис, Татьяна Александровна; Кан, Сергей Людовикович; Копытина, Наталья Валерьевна (Medicine in Kuzbass, 2025)
The article analyzes the use of information technology in the training of medical personnel from the late 80s of the last century to the present. The problems of implementation are considered and the effectiveness of information technologies in the educational process is shown. The purpose of the study is to study the use of information technologies in the educational process and to evaluate their role in the system of medical personnel training. Materials and methods. The research material is information technologies used in the training of medical personnel in a higher educational institution of a medical profile from the late 80s of the last century to the present. The following research methods were used: analysis of literary sources, copying of data from curricula of specialties and working curricula of departments, questionnaire method, analysis and interpretation of the data obtained. The results and their discussion. The importance of information technology in healthcare is very great. They improve the quality of medical care for the population and improve the work of medical organizations. In recent years, Russia has been carrying out the digitalization of the social sphere, including the healthcare system, and medical organizations use a large number of information programs. In accordance with the requirements of the time, a graduate of a medical university must have basic knowledge and skills in working with various information systems, and possess digital competencies. This allows for faster development of the digital environment of both the medical organization and the healthcare system as a whole. The research materials show that new information technologies used in practical healthcare dictate the need for transformation of the educational process. Modern information technologies used in the educational process help students to learn the material more easily and adapt to work more quickly. Conclusion. The transformation of the process of teaching information technologies in the process of training medical personnel depends on the level of development of information technologies in the industry as a whole, the interaction of an educational organization with medical organizations and regional health management bodies, the state of the material and technical base, and the training of the teaching staff of an educational organization. The transformation of the process of teaching information technologies in the educational process allows for improved practical training of graduates for working in the digital environment of medical organizations and, as a result, ensures a higher level of specialists in the field of public health.